Limit state design approach for the safety evaluation of the foundations of concrete gravity dams - Braga Farinha, M. L. (2015)
The application of the limit state design (LSD) in the geotechnical area has increased over the last two decades, but this approach is not yet widely used in dam safety evaluation. This study aims to widen the use of the LSD application for large dams, in particular concrete gravity dam foundations. This paper starts with a brief reference to the LSD approach in recently published guidelines for dam design, followed by a detailed description of the LSD formulation when applied to the foundation of concrete dams. The relevance of the joint application of the concepts of ultimate limit states and of numerical methods is highlighted. Comments are made regarding the criteria adopted in order to determine the characteristic values of the material mechanical properties, with an emphasis on discontinuities, taking into account the spatial variability. The sliding safety assessment of the foundation of a concrete gravity dam using the LSD and a discrete element model, both in persistent and in an accidental design situation, is presented. Results led to the conclusion that the LSD methodology may be followed for dam foundation design with the partial factor values prescribed in Eurocode 7.